Cognitive Sequelae of Central-Variant Posterior Reversible Encephalopathy Syndrome (PRES) - Joseph Seemiller; Muhammad Taimur Malik (Case Reports in Neurological Medicine)
Introduction. Although the posterior reversible encephalopathy syndrome (PRES) is often associated with headache and visual changes, central-variant PRES can be difficult to clinically diagnose in a patient with alteration of consciousness. Central-variant PRES has been previously described in the literature affecting subcortical white matter and the brainstem. Case Presentation. We describe a case presenting with hypertension (192/98) and altered level of consciousness requiring intubation. She was ultimately found to have extensive symmetric cortical and subcortical edema, with extensive involvement of bilateral thalami, consistent with central-variant PRES. Her mentation rapidly improved with blood pressure management. Confirmation of the diagnosis of central-variant PRES was made on repeat brain imaging. Our case is unique in demonstrating dramatic central white matter changes and their reversibility on repeat imaging six days later. Finally, persistent cognitive deficits at follow-up four months later are described. Conclusion. Atypical presentations of PRES, involving alterations in levels of consciousness, can be difficult to clinically diagnose. A thorough differential diagnosis is even more important in cases of PRES with atypical imaging. Recognition of the diagnostic patterns of PRES on brain imaging, with prompt reversal of the causative factors, is crucial for the appropriate care of these patients. The long-term sequelae, which could include cognitive deficits, are poorly studied and understood.